"This One Is 400 Libyan Dinars, This One Is 500": Insights from Cognitive Human Capital and Slave Trade. Issue 2 (3rd April 2018) - Asongu, Simplice A.; Kodila-Tedika, Oasis
ABSTRACT: One of the most disturbing contemporary episodes in human history that has been decried globally is the recent Libyan experience of slave trade, where migrants captured end-up being sold as slaves. We contribute to the understanding of this phenomenon by investigating the role of cognitive human capital on slave trade. To this end, we use the historic intelligence and slave trade variables, respectively, as the independent and outcome variables of interest. Our findings show a negative relationship between slave trade and cognitive human capital. Hence, the slave trade is more apparent when cognitive human capital is low. The Ordinary Least Squares findings are robust to the control for outliers, uncertainty about the model and Tobit regressions. We substantiate why from the perspective of massive sensitization and education, the non-contemporary relationship between cognitive ability and slave trade established in this study has contemporary practical policy relevance in efforts to stem the tide of clandestine travel to Europe through countries in which clandestine migrants are captured and sold as slaves.